Shear strength of reinforced concrete deep beams with large openings strengthened by external prestressed strands. (December 2020) - Khalaf, Mohammed Riyadh; Al-Ahmed, Ali Hussein Ali
Abstract: This study is performed to examine the effectiveness of using externally prestressed strands for shear strengthening of reinforced concrete (RC) deep beams with large openings. A total of nine RC deep beams with large openings having a rectangular cross-section of 150 × 400 mm and a total length of 1600 mm were constructed and tested up to failure under three-point bending. The studied parameters were the opening ratio and the strengthening scheme using prestressed strands. These beams were divided into three groups depending on strengthening scheme, Group I (unstrengthening), Group II (strengthened by horizontal external strands) and Group III (strengthened by vertical external strands). For each group, three opening ratios were adopted (0.4, 0.6 and 0.8). Two large rectangular openings, one in each shear span were placed symmetrically about the centerline of the beam. Externally horizontal prestressed strands scheme was found very effective in upgrading the shear strength of RC deep beams. The ultimate strength gain caused by the horizontal scheme of strengthening was in the range of 32–53%. Also, this scheme of strengthening resulted in a remarkable decrease in tension reinforcement strain for all opening ratios. The reduction in tension reinforcement strain was in the range of 60–91%. While, the vertical scheme of strengthening had an insignificant effect on tension reinforcement strain. On the contrary, this scheme of strengthening showed a notable decrease in stirrups strain in the range of 142 – 158 %. Analytical solution using the strut and tie model (STM) has been modified to adjust the schemes of strengthening strands. The predicted shear strengths of RC deep beams with openings with and without strengthening were verified with the experimental results with a convergence of 0.93 on average.